Bubble impingement and the mechanisms of heat transfer enhancement - Donoghue, David B (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
Fluid agitation and mixing ensuing from two phase flow has an important role to play within two phase flow heat exchangers, which are at the forefront of energy conversion. Within these environments, vapour bubbles may impinge against the heat exchange surfaces of the device, with this behaviour thought to directly affect convective heat flow. Investigations into this complex fluid structure interaction have begun in recent years, however, the mechanisms involved in bubble movement are dynamic and complex and, in some cases, poorly understood. Although numerous studies exist for free rising bubbles, research into their effects on heat transfer is limited; even fewer studies have been performed in relation to bouncing bubbles. This study evaluates the convective heat transfer from a horizontal, heated downward facing surface due to the effect of a single air bubble rising through distilled water and impacting and bouncing on the surface. In order to evaluate the current state of the art, a comprehensive review of the relevant literature has been performed.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin